SCHOOL-BASED PHYSICAL ACTIVITY INTERVENTIONS: EFFECTS ON MOTOR COMPETENCE AND HEALTH-RELATED OUTCOMES IN CHILDREN – A SCOPING REVIEW - Durlević, Marija; Durlević, Slavka (Sport - nauka i praksa, 2026)
Insufficient physical activity and declining levels of motor competence among children represent a significant public health concern. Accordingly, the aim of this scoping review was to map and synthesize the existing evidence on the effects of school-based physical activity and physical education interventions on children’s motor competence, while considering their potential role within a public health framework. This scoping review was conducted in accordance with the PRISMA-ScR guidelines. A systematic literature search was carried out across four electronic databases (PubMed, Web of Science, Scopus, and Google Scholar). Two independent reviewers assessed the studies based on predefined eligibility criteria, and disagreements were resolved by consensus. A total of eighteen studies were included in the final review. The methodological quality of the included studies was assessed using the Effective Public Health Practice Project (EPHPP) quality assessment tool. The majority of the included studies demonstrated positive effects of school-based interventions on motor competence, particularly in the domains of locomotor and manipulative skills. Interventions of longer duration, as well as those characterized by structured and developmentally appropriate activities, also showed positive and more pronounced effects. School-based physical activity and physical education interventions represent an effective public health strategy for improving motor competence and supporting healthy development in childhood. Strengthening the quality and consistency of school-based movement programs may contribute to long-term health benefits and disease prevention at the population level. This scoping review identifies gaps in the existing literature and proposes directions for future research in the field of school-based motor competence interventions.